Flexibility Strategy and Postponing Work on Community Service Employees during Activities Work for Home (WFH) during the Covid - Noer Soetjipto; Sulastri Sulastri; Arif Hidayat (UIN Sunan Gunung Djati, 2022)
The application of flexible management through the work from home (WFH) policy has created the potential for quite a lot of community service jobs that have been going on so far. The research which aims to analyze management flexibility is related to the implementation of flexible management with potential delays in work during the Pandemic period where every employee does daily work pickets. Sampling took 52 government employees in the public service sector by purposive incidental sampling. Data were collected through the thurstone scale in the form of closed choice, and analyzed through inferential analysis techniques as a proof of the hypothesis. The results of the study describe the potential for work delays by 50% of employees who take advantage of rotating work days, and 49% of employees who tend not to use the excess flexibility of leadership policies and 64% of employees who may be low or sometimes able to use hours. work during the pandemic. The potential for delays is mostly done by taking advantage of working time or delaying if the employee is outside the daily work picket even though it is still within the effective working hours of the week. The results of hypothesis testing through chi suare obtained a value of 2 of 30.617 (df 6; 5%) obtained a probability value of 0.000 (p < 0.01), which means that there is a very significant correlation between the application of management during the pandemic through work from home activities (WFH). ) with the potential for delaying the completion of public service tasks by government employees in the public service sector.